Cultural identity and childhood – an integrated curricular experience from Azorean plays - Vaz, Alexandre Fernandez; Peters, Leila; Losso, Cristina Doneda (Journal of Physical Education (Maringá), 2008)
This study intends to present an integrated curricular experience carried out with the third year of a primary public school in Florianópolis – Santa Catarina which was entitled a cidade (the city). Regarding Physical Education the Azorian plays were taken into account discussing memory and history. 18 classes were observed in the year 2000 through a participatory way and specific instruments. Activities started with a visit to Museu do Brinquedo of UFSC (Universidade Federal de Santa Catarina) when children knew Franklin Cascaes’ sculptures about Azorian plays. Children organized and experienced several plays. The analysis of data allows us to point out the following questions: (1) the reorganization of the memory, of the collective image and of the identities related to Azorian tradition corporal practice;(2) the different childhood places; (3) the different periods of teaching and learning; (4) the distinct and fluctuating expressions of style.